City for Empire : An Anchorage History, 1914-1941 - Jones, Preston, 1966- (Book collections on Project MUSE., 2010)
First settled in 1915, Anchorage, Alaska, was founded with the American empire in mind. During World War I, it served as a conduit through which coal could be shipped to the Pacific, where the US Navy was engaged with Japan. Decades later, during World War II, Anchorage became an equally important site for the defense of the mainland and the projection of American power. City for Empire tells the story of Anchorage's development in that period, focusing in particular on the international context of the city's early decades and its surprisingly diverse inhabitants. A thorough yet accessible rea.